Research on Plasma Chemistry Reactions in C3H6/NO/O2/N2 Mixture Gases - 蔡忆昔 张乐夫 王军 赵卫东 王静 (Plasma science & technology, 2010)
A DBD-type （dielectric barrier discharge） NTP （non-thermal plasma） reactor was designed and an experimental system was established, in order to study the mechanism of plasma chemistry reactions in a gas mixture of C3H6/NO/O2/N2. This paper is focused on a. the effects of the initial concentrations of both NO and 02 upon NO conversion rate and the variations of NOx and 03 concentrations versus SED （specific energy density） when mixed gases of NO/O2/N2 passed the NTP reactor; b. the effects of the initial concentration of C3H6 upon NO oxidation and reduction reactions in mixed gases of NO/N2/CaH6 and NO/N2/O2/C3H6. The conclusions drawn are as follows, a. When the mixed gases of NO/O2/N2 passed the NTP reactor, NO was simultaneously involved in oxidation and reduction reactions with the former dominant and NO2 concentration increased at the NTP reactor outlet. The NO conversion rate decreased with the increase of the initial concentration of NO and 02, the O3 concentration firstly increased and then decreased with the increase in SED value, b. NO reduction reaction was very weak and energy consumption was very high in a mixed gases of NO/N2. However, when C3H6 was added, the NO conversion rate was significantly increased. When 63H6 was added to the mixed gases of NO/O2/N2, the NO conversion rate was significantly increased and the energy consumption was considerably reduced.